Impact of a Prenatal Vitamin D Supplementation Program on Vitamin D Deficiency, Rickets and Early Childhood Caries in an Alaska Native Population - Rosalyn J. Singleton; Gretchen M. Day; Timothy K. Thomas; Joseph A. Klejka; Christine A. Desnoyers; Melanie N. P. McIntyre; David M. Compton; Kenneth E. Thummel; Robert J. Schroth; Leanne M. Ward; Dane C. Lenaker; Rachel K. Lescher; et al. (Nutrients, 2022)
Background: Early childhood rickets increased in Alaska Native children after decreases in vitamin D-rich subsistence diet in childbearing-aged women. We evaluated the impact of routine prenatal vitamin D supplementation initiated in Alaska’s Yukon Kuskokwim Delta in Fall 2016. Methods: We queried electronic health records of prenatal women with 25(OH) vitamin D testing during the period 2015–2019. We evaluated 25(OH)D concentrations, vitamin D3 supplement refills, and decayed, missing, and filled teeth (dmft) scores and rickets in offspring. Results: Mean 25(OH)D concentrations increased 36.5% from pre- to post-supplementation; the percentage with deficient 25(OH)D decreased by 66.4%. Women with ≥ 60 vitamin D3 refill days had higher late pregnancy 25(OH)D concentrations than those with no refill days (p < 0.0001). Women with late pregnancy insufficient 25(OH)D concentrations had offspring with higher dmft scores than those with sufficient 25(OH)D (RR 1.3, p < 0.0001). Three children were diagnosed with nutritional rickets during the period 2001–2021, and none after 2017. Conclusions: These findings suggest that prenatal vitamin D supplementation can improve childhood outcomes in high-risk populations with high rates of rickets.